Dental Decay Phenotype in Nonsyndromic Orofacial Clefting. (September 2017) - Howe, B.J.; Cooper, M.E.; Wehby, G.L.; Resick, J.M.; Nidey, N.L.; Valencia-Ramirez, L.C.; Lopez-Palacio, A.M.; Rivera, D.; Vieira, A.R.; Weinberg, S.M.; Marazita, M.L.; Moreno Uribe, L.M.
Although children with oral clefts have a higher risk for dental anomalies when compared with the general population, prior studies have shown conflicting results regarding their dental decay risk. Also, few studies have assessed dental decay risk in unaffected relatives of children with clefts. Thus, the question of increased risk of dental decay in individuals with oral clefts or their unaffected relatives is still open for empirical investigation. This study characterizes dental decay in the largest international cohort to date of children with nonsyndromic clefts and their relatives, as compared with controls, and it addresses whether families with oral clefts have a significantly increased risk for dental decay versus the general population. A total of 3, 326 subjects were included: 639 case probands, 1, 549 unaffected relatives, and 1, 138 controls. Decay was identified from in-person dental examinations or intraoral photographs. Case-control differences were tested with regression analysis. No significant differences were shown in percentage decayed and filled teeth and decayed teeth in the primary dentition (dft, dt) and permanent dentition (DFT, DT) in cases versus controls. In the cleft region, no significant differences were seen in primary or permanent decay (dt, DT) when compared with controls. No difference was found with regard to cleft type and percentage dft, dt, DFT, and DT in case probands. Nonsignificant differences were found in unaffected siblings and parents versus controls (primary and permanent dentitions). Collectively, these findings indicate that individuals with nonsyndromic oral clefts and their families do not have a higher dental decay risk as compared with the general population. These results suggest that either genetic or environmental factors underlying a higher susceptibility for dental anomalies do not increase caries risk or that the seemingly higher risk for dental decay associated with increased dental anomalies in case probands may be superseded by possible greater access to dental care.